Metal cation exchanged montmorillonite K10 (MMT K10): Surface properties and catalytic activity - Farah W. Harun; Enas A. Almadani; Salina Mat Radzi (International Journal for Scientific Research and Development, 2024)
Volume:3 Issue:3